Nazira TEACHING VOCABULARY THROUGH TOTAL PHYSICAL RESPONSE: TEACHING VOCABULARY THROUGH TOTAL PHYSICAL RESPONSE - Abraimova, Nazira (Журнал иностранных языков и лингвистики, 2022)
One method for helping students learn a language (in most cases uses to learn vocabulary) is known as “Total Physical Response” (TPR). This method allows students to pick up the foreign language through listening, reading, visual sources, and actions. It is now being practiced successfully by many teachers all over the world. However, this method limited: it is not known to be used much beyond beginner level.